Multi-Agent Systems for Society 8th Pacific Rim International Workshop on Multi-Agents, PRIMA 2005, Kuala Lumpur, Malaysia, September 26-28, 2005, Revised Selected Papers - Lukose, Dickson (Lecture Notes in Artificial Intelligence, 2009)
This book constitutes the thoroughly refereed post-conference proceedings of the 8th Pacific Rim International Workshop on Multi-Agents, PRIMA 2005, held in Kuala Lumpur, Malaysia, in September 2005. The 29 revised full papers and 2 keynote papers presented were carefully reviewed and selected from numerous submissions. The papers address many current topics in multi-agent research and development, ranging from theoretical and methodological issues to various applications in different fields.